Multipath Parallel ICCP Underwater Terrain Matching Algorithm Based on Multibeam Bathymetric Data - Hanbing Wang; Xiaosu Xu; Tao Zhang (IEEE Access, 2018)
Using the underwater terrain for assisted navigation is a popular research direction for autonomous underwater vehicle navigation technology. The iterated closest contour point (ICCP) algorithm is one of the classic matching algorithms in underwater terrain assisted navigation. However, the traditional ICCP algorithm is not suitable for the case of large initial error of inertial navigation system (INS) because it easily leads to a total match failure. This failure brings a great challenge to an underwater terrain matching system. In this paper, the improved ICCP underwater terrain matching algorithm, a multipath parallel ICCP algorithm, is proposed. The improved algorithm is based on multibeam bathymetric data acquired by the multibeam echosounder that is one of the main instruments of water depth measurement. The data points at the center and both sides of the edge of the swath sounding data are chosen to comprise three paths that are fully utilized by the improved algorithm. Computer simulation is used to evaluate the proposed algorithm in two terrain differences areas. Simulation results verify the effectiveness of multipath parallel ICCP algorithm. The proposed algorithm can effectively solve the problem of matching divergence caused by large initial errors of INS and obtain higher location accuracy.